PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DISDUKCAPIL KABUPATEN MURUNG RAYA PROVINSI KALIMANTAN TENGAH - Susiladewi -; periyadi - (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, This research aims to determine whether there is influence of motivation and work discipline on the performance of employees Disdukcapil Murung Raya District either partially or simultaneously. The method used in this study is quantitative research is a research model that requires the existence of the calculation of the numbers, while the approach used is a survey approach that is the research that takes samples from the population and use the questionnaire as the main data collection tool. The results of this research indicate that the variables of motivation and work discipline significantly influenced and changes in the direction of performance employees Disdukcapil Murung Raya regency. This means that if the level of influence of motivation and discipline perceived higher, then lead to higher performance as well.